Video In Situ Snowfall Sensor (VISSS) data for Hyytiälä on 2025-10-17 - Pfeifer, Nils; Maahn, Maximilian; Moisseev, Dmitri (In: Pfeifer, N et al. (2026): Video In Situ Snowfall Sensor (VISSS) data for Hyytiälä (November 2024 - December 2025) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.994111, 2026)
The VISSS is a camera system recording precipitating snowfall from two perspectives. Here, movies and images of falling precipitation particles are provided for one day at station Hyytiälä. For further details on the VISSS see Maahn et al. (2024).
Keywords: In-situ experiment; precipitation; snowfall measurements